Second language learners' expectation of classroom communication - Hashim, Che Noraini; Kayode, Bakare Kazeem; A. Rahman, Oseni (2011)
Effective classroom teaching is more often than not aided by effective classroom communication of the teachers or instructors. Teaching behaviours have been studied in various arenas in higher education. Many studies have found that while most universities offer a traditional face-to-face communication format to deliver their courses, few offer them in online communication format. Since communication in the classroom is mostly oral rather than written, many students equate being able to learn in classroom with the effective communication of the instructor. That is, the appropriate use of the instructional language by the lecturer. This study, therefore, investigated the perceptions and expectations of students from two facilities in TWINTECH (Faculty of Business and Faculty of Music) of classroom communication. This research was conducted using a quantitative research approach; 150 students both local and international participated in the study; the data were gathered via a self-administered questionnaire. Principal component analysis (PCA) was used to validate both the questionnaire items and item construct (latent variables). The Pearson product moment correlation coefficient was used to examine the relationship between the age of the respondents and the learners’ perception of classroom communication score, the independent t-test was used to investigate the differences in students’ perception with regard to their gender. The findings show that most students in this study have a positive perception towards classroom communication and that of those who have a negative perception, it is as a result of their lack communication ability in the class, and that better students have a higher positive perception towards classroom communication than the weak ones.